Health care sector: empirical relationship between patient care and ability to pay - ROBERT, MR. P. WILLIAM; M, MS. FATHIMA PARVEEN (The journal of contemporary issues in business and government, 2020)
Health care industry is witnessing a potential growth sector for investment. Many potential investors wants to startup the enterprise and became the Entrepreneur in this sector.The research paper titled Empirical relationship between Patient care and ability to pay. The objective is to study the impact of Patient care on the ability to pay. Descriptive research is applied using convenience method of sampling with 102 patient. The majority of respondents were Female and their age group is 18-25 years. The tools used is mean analysis, frequency analysis, T-test, Anova and Regression analysis. It is found that factors influencing the patient care is influencing the ability to pay and there is no significant difference between demographic variable with respect to Patient care and ability to pay.